2019
DOI: 10.1186/s13071-019-3680-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Trypanosoma brucei gambiense in naturally infected dogs in Nigeria

Abstract: Background Animal trypanosomosis is endemic in Nigeria, while the human disease caused by Trypanosoma brucei gambiense is rarely reported nowadays after efforts to bring it under control in the 20th century. The University of Nigeria Veterinary Teaching Hospital (UNVTH) is a reference centre located within the Nsukka area and serves Enugu and neighboring states, Benue, Kogi, Anambra and Delta. Among dogs presented to the UNVTH with canine trypanosomosis, T.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 26 publications
7
24
0
Order By: Relevance
“…This hypothesis is confirmed by the detection of T. b. gambiense in animals of the three HAT foci. The identification of natural infections of T. b. gambiense in pigs, sheep, goats and dogs confirm results obtained in some West and Central African HAT foci [ 8 , 9 , 16 , 17 , 28 , 40 – 43 , 50 , 51 , 56 ]. Moreover, experimental studies have demonstrated that all animal species found with T. b. gambiense can maintain this parasite for several months with the possibility of completing its cyclical transmission [ 35 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This hypothesis is confirmed by the detection of T. b. gambiense in animals of the three HAT foci. The identification of natural infections of T. b. gambiense in pigs, sheep, goats and dogs confirm results obtained in some West and Central African HAT foci [ 8 , 9 , 16 , 17 , 28 , 40 – 43 , 50 , 51 , 56 ]. Moreover, experimental studies have demonstrated that all animal species found with T. b. gambiense can maintain this parasite for several months with the possibility of completing its cyclical transmission [ 35 ].…”
Section: Discussionsupporting
confidence: 85%
“…Previous investigations revealed several domestic and wild animal species as potential hosts of T. b. gambiense in West and Central African HAT foci [ 8 , 9 , 16 , 17 , 28 , 40 42 , 44 , 50 , 51 ]. For instance, natural infections of T. b. gambiense have been reported in sheep and goats in Cameroon, Equatorial Guinea and Congo [ 8 , 41 , 44 , 50 ], in pigs in Cameroon and Liberia [ 16 , 42 , 51 ], and in dogs in Liberia and Nigeria [ 16 , 56 ]. Besides these domestic species, several wild animal species have been also reported with natural infections of T. b. gambiense in Central African HAT foci [ 10 , 17 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…The death of the dogs in the infected untreated control dogs within 28 days PI can be due to the parasite's immunosuppressive effects, hence not allowing the dogs enough time to produce sufficient antibodies to fight the invading parasite. The clinical signs of corneal opacity, pale mucosae, staggering movement, ocular discharges, weakness and lethargy were consistent with findings of previous researchers (Ezeh et al, 2009;Umeakuana et al, 2019). The trypanocides cleared the parasitaemia following treatment by day 14 PI indicating that diminazene aceturate (DA) and isometamidium chloride (IMC) were efficacious in the treatment of T. brucei in dogs.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies on trypanosomiasis transmission have been conducted in some parts of Nigeria [ 10 , 11 , 22 ]. However, to date, there is no published report on the prevalence of AAT in Kwara state.…”
Section: Introductionmentioning
confidence: 99%